2015
DOI: 10.3126/ijssm.v2i3.12721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Media Marketing on Small Scale Business Performance in Ota-Metropolis, Nigeria

Abstract: The purpose of this study is to examine the effect of social media marketing on small scale business performance. In today's social media driven environment, it is essential that small businesses understand facebook, twitter, and the strategies behind using social media for growing their business. Unfortunately, many small businesses do not have a strategy when they begin using social media. The objectives of this study include the following: to determine how effective employee training about social media of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 23 publications
4
27
0
1
Order By: Relevance
“…She acknowledges that the adoption of social media is high because it is a cheap technique of digital marketing, and also reaches many potential customers who are on social media. The results are consistent with the studies done by Srinivasan et al (2016), Adegbuyi et al (2015) and Jagongo and Kinyua (2013) who indicated that social media creates brand awareness that results in strong influence on customer acquisition and retention. Cesaroni and Consoli (2015) further acknowledge that the decision to adopt social network is inspired by the willingness of the entrepreneur to create a new business model, characterised by interactivity, openness to clients, collaboration and visibility.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…She acknowledges that the adoption of social media is high because it is a cheap technique of digital marketing, and also reaches many potential customers who are on social media. The results are consistent with the studies done by Srinivasan et al (2016), Adegbuyi et al (2015) and Jagongo and Kinyua (2013) who indicated that social media creates brand awareness that results in strong influence on customer acquisition and retention. Cesaroni and Consoli (2015) further acknowledge that the decision to adopt social network is inspired by the willingness of the entrepreneur to create a new business model, characterised by interactivity, openness to clients, collaboration and visibility.…”
Section: Introductionsupporting
confidence: 92%
“…Findings reveal that small scale business operators use social media to display information like the services they render or products they sell, the price of their products, their location or contact details, their business logos and some even go as far as stating the quality of the product. Most respondents claim that placing information about their business online has created more awareness, brought in more customers (Srinivasan et al, 2016;Adegbuyi et al, 2015;Jagongo & Kinyua, 2013), boost sales and profits (Omondi, 2017) all the while eliminating the need for one-on-one advertising. The effects of social media marketing varied from one respondent to the other.…”
Section: Use Based On Information Placementmentioning
confidence: 99%
See 2 more Smart Citations
“…Kumar et al [24] referred to social media as the undisputed king of internet due to its significance in the global community. According to Adegbuyi et al [25], it is essential that smalland medium-sized businesses understand the use of social media platforms, such as Facebook and Twitter, and the strategies behind using social media for growing their businesses. Unfortunately, this is not the case, as many small businesses do not have a strategy when they begin using social media.…”
Section: Review Of Literaturementioning
confidence: 99%